Pneumocystis Carinii Infection of the Small Intestine in a Patient with Acquired Immune Deficiency Syndrome. Issue 5 (25th January 2016) - Carter, Timothy R.; Cooper, Philip H.; Petri, William A.; Kim, C. Kurtis; Walzer, Peter D.; Guerrant, Richard L.
Abstract : The authors describe a patient with acquired immune deficiency syndrome (AIDS) who presented with an acute abdomen. A plaque-like tumor of the small intestine was resected and found to consist of masses of Pneumocystis carinii organisms. The organisms also exhibited a perivascular and intravascular distribution. Identical changes were found in regional lymph nodes. In addition to silver stains and electron micros-copy, an immunohistochemical method for the demonstration of P. carinii was employed. The technique may have advantages over silver staining, as it identifies trophozoites in addition to cysts. A review of the literature concerning extraplumonary pneumocystosis indicates that affected patients nearly always have concurrent pulmonary infection. The pattern of organ involvement and the finding of perivascular and intravascular organisms are consistent with lymphatic or hematogenous dissemination from the pulmonary focus. Pulmonary pneumocystosis was not documented in the patient described herein, although there were radiographic densities in one pulmonary lobe.